2016
DOI: 10.14257/ijsia.2016.10.4.28
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Certificateless Signcryption from Bilinear Pairings

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…25 Besides, the schemes 19,21 are shown vulnerable to several attacks, 17,20 respectively. Further, the schemes 22,24 are shown secure under hypothetical ROM, thereby deficiency in practical implementation.…”
Section: Results Analysis and Comparisonsmentioning
confidence: 99%
See 2 more Smart Citations
“…25 Besides, the schemes 19,21 are shown vulnerable to several attacks, 17,20 respectively. Further, the schemes 22,24 are shown secure under hypothetical ROM, thereby deficiency in practical implementation.…”
Section: Results Analysis and Comparisonsmentioning
confidence: 99%
“…Table shows a detailed runtime comparison among several related CLSC schemes where Luo‐Wan requires major cost of 19.27 ms, and the proposed scheme needs minor cost of 3.72 ms. It can be observed that the computation overhead of the proposed CLSC is approximately 27 % of Reference , 23 % of Reference , 49 % of Reference , 25 % of Reference , 52 % of Reference , 20 % of CLSC scheme . Besides, the schemes are shown vulnerable to several attacks, respectively.…”
Section: Performance Measurementmentioning
confidence: 98%
See 1 more Smart Citation
“…Thereafter efforts were taken by many researchers to address the above issue but it did not proved to be successful. In order to overcome all these previous drawbacks a remarkable milestone was achieved by Hongzhen Du [19] in 2016.He proposed an efficient certificateless signcryption scheme which is secured using random oracles and where message confidentiality, signature unforgability, public verifiability and forward secrecy are taken care of. Moreover this scheme also achieves smaller ciphertext size and hence could be used with smaller bandwidth.…”
Section: Certificateless Signcryption Schemes With Bilinear Pairingmentioning
confidence: 99%
“…In [ 10 ], elliptic curve-based signcryption scheme, from the standardized signature was proposed ensuring not only security but also minimizing computation and communication overhead. However, to increase security without pairing operation, cryptographic hash function was designed in [ 11 ]. However, the scheme was proven to have certain security weakness.…”
Section: Introductionmentioning
confidence: 99%